Resposta :
Olá!
--
↔ Explicação numérica :
[tex] \\ { \large \displaystyle \sf { - 2 - \left \{ 5 - [3 - ( - 3 - 1)] \right \} = }}[/tex]
[tex]{ \large \displaystyle \sf { - 2 - \left \{ 5 - [3 - ( - 4)] \right \} = }}[/tex]
[tex]{ \large \displaystyle \sf { - 2 - \left \{ 5 - [3 + 4] \right \} = }}[/tex]
[tex]{ \large \displaystyle \sf { - 2 - \left \{ 5 - [7] \right \} = }}[/tex]
[tex]{ \large \displaystyle \sf { - 2 - \left \{ 5 -7 \right \} = }}[/tex]
[tex]{ \large \displaystyle \sf { - 2 - \left \{ - 2 \right \} = }}[/tex]
[tex]{ \large \displaystyle \sf { - 2 + 2 = }}[/tex]
[tex]{ \green{ \boxed{ \boxed{ \pink{{ \large \displaystyle \sf { \: \: 0 \: \: }}}}}}} \\ \\ [/tex]
↔ Então, teremos como resposta :
[tex] \\ { \green{ \boxed{ \boxed{ \pink{{ \large \displaystyle \sf { \: \: 0 \: \: }}}}}}} \\ [/tex]